Assessing EPAP lexical features: A corpus-based study - María José Marín; Camino Rea Rizzo (Quaderns de Filologia: Estudis Lingüístics)
The features of specialised languages have been extensively described by scholars in the literature. Amongst them, Enrique Alcaraz’s work stands out as an exhaustive and comprehensive description of EPAP at all linguistic levels: lexical, syntactic, semantic and pragmatic. This research aims to provide a bottom-up assessment of his description on a lexical level through the implementation of corpus-based techniques on two specialised corpora of legal and telecommunications English. The results support Alcaraz’s portrayal as regards term usage, the relevance of sub-technical vocabulary, the peculiarities of Latin single and multi word terms in legal English and the significant presence and usage of abbreviations in telecommunications English.